PROSPECTIONS OF ORGANIZATIONAL OPTIMIZATION IN THE APPLICATION OF LAIA ENVIRONMENTAL TOOL: A CASE STUDY (ADMPG Journal, 2023)
AbstractThis article aims to demonstrate improvements in an organizational environment using the environmental tool LAIA - Survey of Environmental Aspects and Impacts in a company providing electrical maintenance services and power grids. The spreadsheet that integrates this tool, besides covering the aspects and impacts of the administrative sector, contemplates the current form of control and the proposal of corrective actions to mitigate or eliminate the environmental impact, allowing case study analysis regarding the organization's Environmental Management. In addition, the methodological aspects made it possible to verify the bibliographic information survey, in order to corroborate and adapt the practices found in the study. Of qualitative character and focusing on the case study in the company, some significant results were raised. LAIA provided benefits such as cost reduction, compliance with legislation, improved organizational image, increased environmental awareness of employees and customers, improved management and, consequently, standardization of production processes and environmental optimization.Keywords: LAIA; Environmental Impacts; Environmental Aspects; Environmental Management.